ECONOMY-MIGRATION, CAUSE AND CONSEQUENCE WHICH INCREASES THE NUMBER OF DIVORCES - Alketa Molla (European Scientific Journal, ESJ, 2015)
The Albanian economy during these 25 years of transition is accompanied by changes. It is true that during this period, has undergone positive changes, but it does not bring any significant improvement in terms of employment growth in the country. Most Albanians, again see immigration as an opportunity for employment, since the country has not been able to find a job, that to provide sufficient income for their families. Youth, the most vital part of society, are the ones who make up the majority of immigrants. The majority of them, once they have a family, and others are parents who want to provide income to raise their children. Immigration contributes positively to the economy of these families, but also has its negative side, in terms of the impact that it has on the relationship between partners in a couple. Living divided between partners, it has created problems in this relationship, being dogged by divorce. So, as a result of a high level of emigration, we have also increased the number of divorces in the country. Low economy brings a host of social problems, which generate from it. These problems lead to an increase in the number of divorces, where most of them make up the pairs, who had only one of the partners or both in emigration. This study was conducted in the region of Elbasan. The data were taken from interviews conducted with partners that have made themselves a request for divorce. For this study also used data from studies carried out by various state institutions, INSTAT and NGOs operating in Albania.